Reassessment of Split-Leg Signs in Amyotrophic Lateral Sclerosis: Differential Involvement of the Extensor Digitorum Brevis and Abductor Hallucis Muscles - Wang, Zhi-li; Cui, Liying; Liu, Mingsheng; Zhang, Kang; Liu, Shuangwu; Ding, Qingyun; Hu, Youfang (Frontiers in Neurology, 2019)
Background: The muscle patterns involved in the “split-leg” syndrome of amyotrophic lateral sclerosis (ALS) remains controversial. We sought to evaluate and reassess the pattern of the extensor digitorum brevis (EDB) and the abductor hallucis (AH) muscles' involvement in split-leg syndrome in ALS. Methods: We recruited 60 consecutive patients with ALS and 25 healthy controls (HCs). Compound muscle action potentials (CMAPs) and F-waves were recorded over the EDB and AH muscles in all subjects. For comparison, we classified patients into two categories based on the presence or absence of lower limbs symptoms. Results: The EDB/AH CMAP amplitude ratio was significantly reduced in patients with affected legs (0.33 ± 0.21, P = 0.007), whereas patients with unaffected legs had a ratio similar to that of the HCs. The EDB/AH ratios for the F-wave latencies, mean F-wave amplitude, mean F/M amplitude ratio, and the persistence of the total repeater F-wave shapes (index Freps) of the EDB-AH, were significantly increased in the affected leg group, whereas the EDB/AH ratio for F-wave persistence was significantly reduced. These findings indicated a greater loss of lower motor neurons (LMNs) innervating the EDB and dysfunction of spinal motoneurons innervating the EDB. In the unaffected leg group, the EDB, but not the AH, F-wave latencies, mean and maximal F/M amplitude ratios, and index Freps were significantly altered. Receiver operating characteristic curve analysis suggested that the EDB F-wave latencies, mean F/M amplitude ratios, and index Freqs (area under the curve [AUC] > 0.8) more strongly differentiated patients with ALS from the HCs compared to the EDB/AH CMAP amplitude ratio (AUC = 0.61). Notably, the EDB maximal F-wave latency and index Freqs reliably differentiated patients with unaffected legs (HCs), with AUCs of 0.83 (95% CI 0.76–0.91) and 0.81 (95% CI 0.72–0.89), sensitivities of 76 and 78%, and specificities of 76 and 78%, respectively. Conclusions: These results suggest preferential EDB compared to AH involvement in the split-leg syndrome of ALS. The EDB maximal F-wave latency and index Freqs robustly differentiated patients with ALS from HCs, which might facilitate an earlier identification of ALS.